Validation and redescription of the hyperiidean amphipod Brachyscelus rapacoides Stephensen, 1925 (Crustacea: Amphipoda: Hyperiidea: Brachyscelidae), a new record of association with the scyphozoan jellyfish Rhopilema nomadica Galil, 1990 (Scyphozoa: Rhizostomeae: Rhizostomatidae) in the Mediterranean Sea - Zeidler, Wolfgang; Douek, Jacob; Rinkevich, Baruch; Gevili, Roy; Goren, Menachem; Galil, Bella S. (Zootaxa, 2018)
The hyperiidean amphipod Brachyscelus rapacoides Stephensen, 1925 is recorded from the scyphozoan jellyfish Rhopilema nomadica Galil, 1990, a new record of association for the genus Brachyscelus, as well as the first record of hyperiid infestation of a non-indigenous scyphozoan host. Because of some past confusion concerning the status of B. rapacoides and the closely related species B. rapax (Claus, 1871) a redescription of B. rapacoides and molecular analysis are provided in order to validate it as a species distinguished from B. rapax.